AFRO-AMERICAN SPIRITUAL SLAVE SONGS: A PSYCHOLOGICAL DIMENSION - Chima, Francis U.; Onu, Mercy A.; Obianika, Chinwe E. (EBSU Journal of Social Sciences and Humanities, 2024)
This paper examined the spirituals, the African American slave songs. Although interest were majorly centred on the psychological dimensions of the songs, the origin, source of nomenclature as well as the features were also looked into. These led to the discovery that the spirituals as Blacks’ sacred-church songs with a hybrid of African-European features were composed in variety of forms within African oral song tradition. As songs born out of emotional feelings of a race, nurtured in the context of ritualized Christian worship for purposes of commenting widely on the circumstance of the Blacks who against self-will found themselves in the American environs, they are means of psychic escape, resistance, struggle and reassurance of hope of freedom for the African Americans.